2022
DOI: 10.1088/1741-4326/ac3f1b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic configuration scans during divertor operation of Wendelstein 7-X

Abstract: Wendelstein 7-X (Greifswald, Germany) is an advanced stellarator, which uses the modular coil concept to realize a magnetic configuration optimized for fusion-relevant plasma properties. The magnet system of the machine allows a variation of the rotational transform (iota) at the boundary. In the latest Wendelstein 7-X operational phase a dedicated configuration scan has been performed varying the rotational transform between magnetic configurations with iota=5/4 and iota=5/5 at the boundary. This paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…During the configuration scan the location of the 5/5 magnetic island chain was moved inside the last closed flux surface, and the island size was varied by changing the control coil current. For these magnetic configuration scan experiments, it has already been reported that the plasma energy increased for the configurations where the 5/5 island chain is close to the plasma boundary but still inside the last close flux surface [5]. However, the reason behind the improved confinement for certain configuration from the scan is not fully understood yet.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…During the configuration scan the location of the 5/5 magnetic island chain was moved inside the last closed flux surface, and the island size was varied by changing the control coil current. For these magnetic configuration scan experiments, it has already been reported that the plasma energy increased for the configurations where the 5/5 island chain is close to the plasma boundary but still inside the last close flux surface [5]. However, the reason behind the improved confinement for certain configuration from the scan is not fully understood yet.…”
Section: Introductionmentioning
confidence: 94%
“…At the start of the magnetic configuration scan experiments specially for the configurations where the magnetic island chain was moved inside the plasma [5], it was observed from the ECE diagnostic that an electron pedestal develops during the plasma buildup phase. Figure 2 shows the ECE time traces for the plasma startup phase, and around 0.27 s in the discharge (marked in figure), it can be seen that the edge channels (lower than 1 keV) start to show change in electron temperature gradient and a transport barrier develops leading to the delayed increase in the core temperature.…”
Section: Electron Temperature Pedestalmentioning
confidence: 99%
See 1 more Smart Citation
“…Ignoring magnetic field errors and field line diffusion, field-lines launched within one island of the five islands in the 5/5 edge will never connect to any of the other islands. Through a combination of coil currents [8] and plasma currents (Pfirsch-Schlüter, bootstrap, ECCD, induced) it is possible to move the locations and affect the size of these 5/5 islands. For the purpose of the analysis here, only vacuum fields generated by coil currents were considered, however, the inclusion of plasma currents should be straightforward as the routines to perform field line following in stellarators with finite beta and net toroidal current already exist [9][10][11][12].…”
Section: Edge Islands In W7-xmentioning
confidence: 99%
“…The different width may be attributed by the change of the magnetic curvature effect and/or the pressure profiles in the plasma edge region. It is observed that the plasma pressure is the highest in the FMM configuration, yielding an increase of the diamagnetic energy (W dia ) and confinement time [34,35].…”
Section: ⊥ Comparison In the Magnetic Configuration Scanmentioning
confidence: 99%